2018
DOI: 10.1097/md.0000000000012484
|View full text |Cite
|
Sign up to set email alerts
|

Pain monitoring and management in a rehabilitation setting after total joint replacement

Abstract: Total hip replacement (THR) and, particularly, total knee replacement (TKR), are painful surgical procedures. Effective postoperative pain management leads to a better and earlier functional recovery and prevents chronic pain. Studies on the control of pain during the postoperative rehabilitation period are not common. The aim of this study is to present results of a perioperative anesthetic protocol, and a pain treatment protocol in use in the Orthopaedic and the Rehabilitation intensive units of our Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…[ 13 , 14 ] Nevertheless, the former researches reported that there was a pain peak within 72 hours after the THA. [ 15 , 16 ] In Lei et al's study, the authors observed that the multiple low-dose dexamethasone can in-depth reduce postoperative pain, improve nausea after surgery, offer extra inflammatory control, increase activity, and decreased postoperative hospital stays. [ 11 ] Therefore, we designed the randomized controlled research to look for the optimal intravenous dexamethasone dose for the treatment of early postoperative pain after the THA.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 , 14 ] Nevertheless, the former researches reported that there was a pain peak within 72 hours after the THA. [ 15 , 16 ] In Lei et al's study, the authors observed that the multiple low-dose dexamethasone can in-depth reduce postoperative pain, improve nausea after surgery, offer extra inflammatory control, increase activity, and decreased postoperative hospital stays. [ 11 ] Therefore, we designed the randomized controlled research to look for the optimal intravenous dexamethasone dose for the treatment of early postoperative pain after the THA.…”
Section: Introductionmentioning
confidence: 99%
“…Pain was assessed after got out of bed and set on a chair in autonomy using the Numeric Rating Scale (NRS). It consists of 11-point numeric scale with a score ranging from 0 to 10 (maximum pain) to evaluate pain intensity after THA [25]. Hip function was assessed using Harris Hip Score (HHS), which is a valid tool ranging from 0 to 100 (maximum function) to assess hip functional status especially after surgery [26].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…NPRS pain assessments will be recorded by participants in a pain diary and carried out daily pre-operatively, postoperatively (thrice daily morning, noon, and evening in hospital until discharge), daily for the first fortnight after surgery, and weekly until the participant exits the study. The NPRS has been used in many studies to monitor pain, for example, in total hip replacement and total knee replacement surgery, 31,32 and compared to the others scales [e.g., visual analogue scale (VAS), verbal rating scale (VRS), and faces pain scale-revised (FPS-R)], has the greatest validity and strength. 31 The NPRS value for patients undergoing total joint replacement is 7.9 -1.7 (mean and standard deviation), and the minimum improvement clinically accepted requires a pain reduction of 20%.…”
Section: Outcome Measuresmentioning
confidence: 99%